(untitled) (Journal of Nepalese Business Studies, 2023)
This research examined the factors influencing consumer adoption of internet banking in Nepal, using the Technology Acceptance Model (TAM) and incorporating trust and government support as additional variables. It presents a comprehensive study focused on Nepal, with data collected through a survey method from 233 participants and analyzed through multiple regressions. The results demonstrated that the perceived usefulness and ease of use significantly impact customers’ intentions to embrace online banking services. However, trust and government support had no significant impact. The insights from this study can aid banks in developing effective approaches to encourage the adoption of online banking in Nepal and potentially serve as a model for other developing nations in the e-commerce and internet banking domains.